Japan and Indonesia Economic Partnership in Food Industries Market - Rohayani, Eka (Global Mind, 2025)
Economic became high foundation in each countries and with Cooperation Agreement can increase GDP (Gross Domestic Product). ASEAN (Association Southeast Asian Nations) as a regional which has potential doing business especially Indonesia with the Implementation of ASEAN Economic Community Blueprint 2025 specifically in Food, Agriculture and Forestry sector for Foreign Investment doing business in Food Industries Market area and Global Economics. Free Trade Agreement (FTA) one of Economic Agreement between two countries for arrange International Trade Cooperation and for encounter of that, Indonesia first time did in work Partnership comprehensive in bilateral Economic International Trade with Japan as a partner between two countries and got a point of Indonesia Japan Economic Partnership Agreement (IJEPA). Indonesia Japan Economic Partnership Agreement (IJEPA) is Economic Agreement between Indonesia and Japan based on the Principle of Economic Partnership Agreement (EPA). This research aims to analyze bilateral cooperation between Japan and Indonesia in Food Industries Market through by companies or multinational enterprises with the concept of John H Dunning (I) Ownership, (II) Location and (III) Internationalization called OLI as International Business Paradigm and Economic Liberalism as International Relations Paradigm with using Qualitative method technical in this writing. Keywords: Implementation ASEAN Economic Community Blueprint 2025, Japan and Indonesia Economic Partnership Agreement, Food Industries Market, John H Dunning Concepts in International Business.